Physical Activity Is Associated With Improved Eating Habits During the COVID-19 Pandemic - Christofaro, Diego G. D.; Werneck, André O.; Tebar, William R.; Lofrano-Prado, Mara C.; Botero, Joao Paulo; Cucato, Gabriel G.; Malik, Neal; Correia, Marilia A.; Ritti-Dias, Raphael M.; Prado, Wagner L. (Frontiers in Psychology, 2021)
The aim of this study was to analyze the association between physical activity and eating habits during the COVID-19 pandemic among Brazilian adults. A sample of 1,929 participants answered an online survey, however 1,874 were included in the analysis. The impact of the COVID-19 pandemic on eating habits was assessed inquiring about participants' intake of fruits, vegetables, fried foods, and sweets during the pandemic. Physical activity was assessed by asking participants about their weekly frequency, intensity and number of minutes/hours engaging in structured physical activities per week. Participants were then stratified into categories based on moderate-to-vigorous intensity (0–30; 31–90; 91–150; 151–300; and >300 min/week) and into active (≥150 min) or inactive (<150 min). Increased sweets consumption was the most commonly reported change to eating habits (42.5%), followed by an increase in the consumption of vegetables (26.6%), fruits (25.9%), and fried foods (17.9%). Physical activity practice was related to lower consumption of fried foods (OR = 0.60; p < 0.001) and sweets (OR = 0.53; p < 0.001). A cluster analysis revealed subjects with higher the level of physical activity was more likely to follow a healthy diet (p < 0.001). Thus, physical activity was positively associated with healthier eating habits. Health authorities must recommend regular physical as a strategy to improve overall health during the COVID-19 pandemic. Future studies should address the physical activity interventions to improve health status during a pandemic.